A Complex of Tools for Teaching Biology in Various General Educational Institutions - Karimova Mavluda Hakimovna (Genius Publishing Group, 2022)
This article describes the complex of biology teaching tools in various educational institutions. In addition, the use of computer and information technologies in biology lessons provides students with the opportunity to simulate biochemical processes occurring in living organisms, and other similar opportunities. Along with this, students will develop narrative skills, the ability to direct their knowledge and conclusions in the environment, draw conclusions from observations and experiments and diagnose primary information obtained in the laboratory
Keywords: Ergonomic; herbarium; taxidermic; entomological